2023
DOI: 10.1002/brb3.2909
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence and trend of anxiety among graduate students: A systematic review and meta‐analysis

Abstract: Objective To evaluate the comprehensive prevalence of anxiety among postgraduates and estimate its changes with a meta‐analysis. Method Systematic retrieval to SAGE, ERIC, EBSCO, Wiley, ScienceDirect, ProQuest, PubMed, EMBASE, and Web of Science database was performed for quantitative studies on the prevalence of anxiety among graduate students published before November 22, 2022. The prevalence of anxiety synthesized with random‐effects model, and subgroup analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Furthermore, our calculations demonstrate that graduates exert a more significant influence on the ABDI. This emphasizes that university graduates have become the primary demographic group experiencing public anxiety, which aligns with findings presented in other studies ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our calculations demonstrate that graduates exert a more significant influence on the ABDI. This emphasizes that university graduates have become the primary demographic group experiencing public anxiety, which aligns with findings presented in other studies ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 91%
“…11 A review study done on the global prevalence and trend of anxiety among graduate students also showed that 34.8% of graduates suffered from anxiety. 12 However, a study conducted among the adult population in Nepal shows a lower prevalence of anxiety which was 16.1%. 3 Among those who had anxiety, the proportion of males was higher than the proportion of females in the study.…”
Section: Discussionmentioning
confidence: 97%
“…Academic posts did not follow this augmentation and, at present, a shortage of academic posts is prevalent globally. This causes job search difficulty following the completion of studies even for those students forced to neglect their personal lives due to the tremendous amount of research work 2,18 . Risks for suicide may await after doctoral studies.…”
Section: Discussionmentioning
confidence: 99%
“…Graduate students are exposed to various types of stress and are thus prone to mental health problems 1 . For example, a systematic review revealed that 34.8% of graduate students from 12 countries suffered from anxiety disorder 2 . The American College Health Association National College Health Assessment found that graduate students have a slightly higher rate of suicidal ideation (12.7%) than undergraduates (12.0%), although rates of depression and anxiety among graduates are slightly lower than those among undergraduates (14.8% vs. 17.3% and 19.5% vs. 22.8%, respectively) 3 .…”
Section: Introductionmentioning
confidence: 99%